2006
DOI: 10.5057/kei.6.2_13
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial Distribution of Visual Attention in Action Video Game

Abstract: In this study, we applied a gaze-contingent window method to measure the spatial distribution of visual attention while playing an action video game. The peripheral visual field of a player was restricted to an area around the gaze by masks with various spatial extents. The quantitative relationship between window size and game performance confirmed that superior players had a wider distribution of visual attention than inferior players. An additional analysis of eye movements showed that the mean length of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…As we discussed earlier, many studies have reported that a size of effective visual field becomes larger with increasing player's expertise of video games [6][7][8]19]. In the visual-masking game task of the present study, the game performance differed among the participants in the car racing game and the falling block game.…”
Section: Discussioncontrasting
confidence: 36%
See 4 more Smart Citations
“…As we discussed earlier, many studies have reported that a size of effective visual field becomes larger with increasing player's expertise of video games [6][7][8]19]. In the visual-masking game task of the present study, the game performance differed among the participants in the car racing game and the falling block game.…”
Section: Discussioncontrasting
confidence: 36%
“…Following previous studies [19,20], we also calculated fixation duration and saccadic amplitude in order to explore eye movement behavior during game play. In the analysis, we used the output of the EyeLink Online Parser which detects saccades, fixations, and blinks.…”
Section: Visual-masking Game Taskmentioning
confidence: 99%
See 3 more Smart Citations